16 kDa vasoinhibin binds to integrin alpha5 beta1 on endothelial cells to induce apoptosis. Issue 5 (May 2018) - Morohoshi, Kazunori; Mochinaga, Ryo; Watanabe, Tsukasa; Nakajima, Ryojun; Harigaya, Toshio
Abstract : Many functions of vasoinhibins have been reported, but its receptor has not been clarified yet. Vasoinhibins, 11–18 kDa N-terminal fragments of prolactin, have anti-angiogenic activity and act on endothelial cells to induce apoptosis and to inhibit migration and proliferation, which are opposite to the effects of prolactin. Although vasoinhibins bind to the prolactin receptor, its binding activity is very weak compared to prolactin. Therefore, in this study, we evaluated the binding activity between 16 kDa vasoinhibin and integrin beta1, alpha5 beta1, alpha1 beta1 and alphaV beta3 to identify a specific receptor for vasoinhibins. Moreover, we examined whether 16 kDa vasoinhibin induced apoptosis through integrin beta1 and alpha5 beta1 in endothelial cells. In this study, binding assays and co-immunoprecipitation experiments demonstrated that 16 kDa vasoinhibin could bind strongly to integrin beta1 and alpha5 beta1. Moreover, neutralizing with integrin beta1 and alpha5 beta1 antibody could inhibit 16 kDa vasoinhibin-induced apoptosis in endothelial cells. These findings suggest that vasoinhibins can act on endothelial cells through integrin alpha5 beta1 to induce apoptosis.